The complete mitochondrial genome of Glossaulax reiniana (Littorinimorpha: Naticidae). Issue 2 (3rd July 2018) - Li, Peng-Yu; Yang, Yi; Li, Yong-Guo; Sun, Shao-E
Abstract: In the present study, the complete mitochondrial genome of Glossaulax reiniana was determined using the next-generation sequencing. The circular genome was found to be 15, 254 bp in length and had an overall nucleotide composition of 30.6% A, 14.1% C, 15.8% G, and 39.5% T. Similar to the typical caenogastropod mitochondrial genomes, it contained 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and a potential control origin. All protein-coding genes started with standard initiation codons (ATA and ATG) and ended by TAA or TAG. The lengths of 12S ribosomal RNA and 16S ribosomal RNA were 948 and 1353 bp, respectively. The largest noncoding region considered to contain the origin of replication was 59 bp in length. The complete mitochondrial genome reported here would provide useful information for molecular phylogeny, genetic conservation, and sustainable management of G. reiniana .